2006
DOI: 10.1200/jco.2006.08.2644
|View full text |Cite
|
Sign up to set email alerts
|

ASCO 2006 Update of Recommendations for the Use of Tumor Markers in Gastrointestinal Cancer

Abstract: For colorectal cancer, it is recommended that carcinoembryonic antigen (CEA) be ordered preoperatively, if it would assist in staging and surgical planning. Postoperative CEA levels should be performed every 3 months for stage II and III disease for at least 3 years if the patient is a potential candidate for surgery or chemotherapy of metastatic disease. CEA is the marker of choice for monitoring the response of metastatic disease to systemic therapy. Data are insufficient to recommend the routine use of p53,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
1,032
5
27

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,387 publications
(1,087 citation statements)
references
References 138 publications
23
1,032
5
27
Order By: Relevance
“…Recently, several studies have reported that patients' genetic profiles are related to the outcomes of cancer therapy (van 't Veer et al, 2002;Ruzzo et al, 2006). In colorectal cancer, since many studies have examined molecular predictors of outcomes during the past decade, TS, DPD, and TP were newly included in 'ASCO 2006 tumour marker guidelines in gastrointestinal cancer' (Locker et al, 2006). Because sufficient supporting evidence is lacking, however, the guidelines recommend that these biomarkers should not yet be used clinically to predict prognosis or treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have reported that patients' genetic profiles are related to the outcomes of cancer therapy (van 't Veer et al, 2002;Ruzzo et al, 2006). In colorectal cancer, since many studies have examined molecular predictors of outcomes during the past decade, TS, DPD, and TP were newly included in 'ASCO 2006 tumour marker guidelines in gastrointestinal cancer' (Locker et al, 2006). Because sufficient supporting evidence is lacking, however, the guidelines recommend that these biomarkers should not yet be used clinically to predict prognosis or treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic and molecular tumor prognostic factors have been proposed to identify patients who may be at risk for recurrence. None of these however, have been sufficiently informative for inclusion in clinical practice [9].…”
Section: Introductionmentioning
confidence: 99%
“…23 Patients with a preoperative serum CEA greater than 5 ng/ml seem to have a worse prognosis, stage for stage, than those with lower CEA levels. In this patient, the immunohistochemical, plasma protein and circulating-cell data revealed interesting patterns at baseline and changes with treatment.…”
Section: Treatment and Managementmentioning
confidence: 97%